Tampilan dalam Buku Teks Bahasa Indonesia Kelas X Kurikulum Merdeka: Analisis Literasi Multimodal - Cici Novi Handini; Liana Rochmatul Wachidah; Hesti Kusumawati (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
This study was conducted because the growing need for multimodal literacy in the digital age requires textbooks to present information through various modes in an integrated manner. The purpose of this study is to identify the configuration of textual, visual, and design features in the Grade X Indonesian Language Textbook under the Merdeka Curriculum, as well as to evaluate their contribution to student comprehension. This study employs a descriptive qualitative approach, with data sources consisting of textbook pages, illustrations, and layout; data were collected through documentation and analyzed using reduction, categorization, and interpretation techniques based on the Kress & van Leeuwen framework. The analysis revealed 47 multimodal findings: 23 textual elements consisting of definitions, explanations, and instructions arranged systematically; 16 visual elements comprising illustrations and QR codes that link learning to digital resources; and 8 design features including layout, typography, and infographics to highlight key information and enhance reader engagement. These three elements complement each other in constructing learning meaning. The text mode is dominant, but the visual and design modes also reinforce meaning representation, reading flow, and learning context. Overall, the textbook has implemented multimodality quite well, although cohesion between modes still needs improvement.